(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يعد نظام الـ B.O.T أحد أهم صور الشراكة مع القطاع العام وإحدى صور التخصيص للمرافق العامة والخدمات، حيث تستخدمه الدول لتحقيق جملة من الاهداف أهمها توفير فرص العمل وتطوير اداء الخدمات العامة والحد من الفساد إضافة إلى الاستفادة من نقل التكنولوجيا أو الخبرات، وكذلك استقطاب رؤوس الأموال أو توطينها، وتعتبر مشاريع الـ B.O.T ذات طابع خاص كونها مشروعات طويلة الأجل، وتقدم خدمات عامة ضرورية للدولة، وتتطلب اموالاً واستثمارات ضخمة، كما أنها بذات الوقت تتطلب تحقيق مجموعة الاشتراطات التي تسهم في جذب المستثمر الوطني أو الأجنبي. Building, Operation and Transfer System( B.O.T) is considered one of the aspects of partnership with the public sector, and an aspect of privatization of public facilities and services, that governments use to achieve a group of services, the most important of which are providing job opportunities, development of public service performance, and limiting of corruption, in addition to technology or expertise transfer, and attracting, or settling capitals. B.O.T projects are long term projects, since they offer general services for the government. These projects need huge amounts of money and investments, and must accomplish some criteria that contribute in attracting the local and foreign investments.